Lack of effect of the abnormal fatty acid metabolism in NC/Nga mice on their atopic dermatitis - Kawamoto, S. (Hiroshima Univ. (Japan)); Kita, M; Hamada, M; Aki, T; Shigeta, S; Suzuki, O; Ono, K (Bioscience, biotechnology, and biochemistry, 2001)
Although clinical evidence has suggested that dysregulated fatty acid metabolism is associated with atopic disorders, the molecular basis for such a correlation remains to be demonstrated. In the present study, we analyzed the fatty acid composition in peripheral blood cells of NC/Nga mice, a model for atopic dermatitis (AD). We found that arachidonic acid significantly accumulated in mice with the AD manifestation. In addition, the leucotriene B 4 -releasing ability upon calcium ionophore A23187 stimulation was potentiated in blood cells. An arachidonic acid accumulation was not apparent in the non-atopic BALB/c strain, but was still observed in healthy NC/Nga mice fed under specific pathogen-free conditions. These results indicate that a disturbed fatty acid metabolism in NC/Nga mice was not a trigger factor for their dermatitis development.